Eimeria telekii n.sp. (Apicomplexa: Coccidia) from Lemniscomys striatus (Rodentia: Muridae): morphology, pathology and phylogeny - Slapeta, J R; Modrý, D; Votýpka, J; Jirků, M J; Oborník, M; Lukes, J; Koudela, B (Parasitology, 2001)
Using a combination of morphological, life-cycle and molecular data, we describe a new apicomplexan parasite Eimeria telekii n.sp. from a striped grass mouse Lemniscomys striatus captured in Kenya. Oocysts are oval to spherical or ellipsoidal, 20.4 x 15.7 (15.5-25.0 x 12.0-20.0) microm with a colourless, smooth and bilayered wall. Sporocysts are ellipsoidal, 11.2 x 7.8 (10.0-12.0 x 7.0-9.0) microm with a small Stieda body and granular sporocyst residuum and contain 2 elongated, banana-shaped sporozoites with a single refractile body. Life-cycle, pathogenicity and host specificity of this parasite were studied in laboratory-bred Lemniscomys barbarus and BALB/c mice. Two asexual stages and the sexual phase took place within the enterocytes of the caecum and colon of L. barbarus but not in inoculated BALB/c mice. An infectious dose of 5000 oocysts caused severe clinical illness and mortality in 2/2 (100%) L. barbarus. Phylogenetic analysis of the small subunit rRNA gene of E. telekii and members of the genera Eimeria, Cyclospora and Isospora placed E. telekii within the eimerian rodent clade.
Keywords: Animals; kolon; RNA ribozomální; Colon; Eimeria; Molecular Sequence Data; Host-Parasite Interactions; Mice; Cecum; interakce hostitele a parazita; Mice, Inbred BALB C; Muridae; myši; stadia vývoje; Phylogeny; RNA, Ribosomal; molekulární sekvence - údaje; Parasite Egg Count; myši inbrední BALB C; Keňa; počet parazitárních vajíček; Life Cycle Stages; zvířata; Kenya; fylogeneze; cékum